2014
DOI: 10.1002/marc.201400145
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐Free Fabrication of polyHIPE Microspheres for Controlled Release of Growth Factors

Abstract: The growth factor bone morphogenetic protein 2 (BMP-2) is utilized in surgical procedures to improve bone regeneration; however, current treatments deliver BMP-2 at amounts greater than 100,000 fold of physiological levels, which increases treatment costs and risk of side effects. Drug-eluting microcarriers developed to improve these therapies have faced significant commercialization challenges including particle size distributions, solvent removal, low encapsulation efficiency, and bioactivity loss. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…Moglia et al developed bone morphogenetic protein 2 (BMP-2) releasing solvent-free ethylene glycol dimethacrylate PolyHIPE microspheres using w/o/w double emulsion system (Moglia et al, 2014a). They reported that while the encapsulation efficiency of their system was up to 73%, but this efficiency reduced to as low as 15% in the processes which require purification.…”
Section: Drug-releasing Polyhipesmentioning
confidence: 99%
“…Moglia et al developed bone morphogenetic protein 2 (BMP-2) releasing solvent-free ethylene glycol dimethacrylate PolyHIPE microspheres using w/o/w double emulsion system (Moglia et al, 2014a). They reported that while the encapsulation efficiency of their system was up to 73%, but this efficiency reduced to as low as 15% in the processes which require purification.…”
Section: Drug-releasing Polyhipesmentioning
confidence: 99%
“…27 Controlling the processing conditions allows precise control over the degree of porosity within the material along with control over the interconnectivity and to some extent pore size. 28 We have recently demonstrated that the mechanical properties of this copolymer system can be finely tuned by changing the monomer ratios. 29 PolyHIPEs are increasingly being used in tissue engineering applications and as cell culture substrates due to their porosity and interconnectivity.…”
Section: -2877/2018/2(2)/026103/19mentioning
confidence: 99%
“…Macroporous polymers have extensive applications in many elds, such as tissue engineering scaffolds, [1][2][3][4] controlled release, [5][6][7][8][9] ion adsorption, 10-13 separation 14,15 and supports for catalysis. [16][17][18][19][20] These applications normally require porous polymers with an open-cell structure.…”
Section: Introductionmentioning
confidence: 99%